Solution‐Processed Selective Area Homoepitaxial Growth of Suspended MAPbX3 (X = Cl, Br) Perovskite Micro‐Arrays. (2nd December 2022) - Zhang, Jinshuai; Li, Chun; Liang, Yin; Song, Jiepeng; Shang, Qiuyu; Zhao, Liyun; Tian, Huifeng; Liu, Lei; Zhang, Qing
Abstract: Suspended nano/microstructures on semiconductor surfaces that can manage light are attractive for various on‐chip and efficiency‐enhanced optoelectronics. Hybrid halide perovskites have shown considerable potential for optoelectronic and photonic applications. However, the ionic and soft lattices of perovskites are sensitive to polar solvents, photons, and heat, limiting the post‐processing of suspended microstructures. Herein, a solution‐processed selective area homoepitaxial growth (SAEG) method is introduced to create well‐ordered, suspended microstructure arrays on the surface of MAPbX3 (X = Br, Cl) single‐crystalline thin films. The suspended micro‐arrays exhibit single crystalline structures and 11.2 fold photoluminescence enhancement compared to the thin‐film substrates. The success of SAEG lies in the making use of perovskite supersaturated HX aqueous solutions that not only repair surface defects induced by lithography but also satisfy homoepitaxial growth kinetics. This study paves a pathway for the fabrication of cost‐effective perovskite surface‐suspended microstructures for efficiency‐enhanced and on‐chip optoelectronic devices. Abstract : Suspended single‐crystalline MAPbX3 (MA = CH3 NH3 +, X = Br or Cl) micro‐arrays on MAPbX3 substrates with controlled locations, orientation, and smooth surface are fabricated via solution‐processed homoepitaxial methods. The success is attributed to making use of the perovskite supersaturated HX aqueous precursor solutions that not only repair surface defects induced by pre‐lithography but also satisfy growth kinetics.